Kinetic Study and Phenomenological Modeling of a Biomass Particle during Fast Pyrolysis Process (2016)
In this project, the main physical and chemical phenomena associated with the pyrolysis of sugarcane bagasse were studied develop a new particle-level model that predicts the evolution of major compounds during the pyrolysis process. The model incorporates dynamics of bubbling within the liquid intermediate phase and their bubbles contributions to the ejection of aerosols. The main physical phenomena occurring during pyrolysis of sugarcane bagasse, pseudo-components, and model compounds (chapters 2-4) were explored. Fof this, new types of reactors (light bulb reactor and hot plate reactor) and visualization methodologies were employed. Notably, a fast camera was used to visualize the growth, nucleation, and size of the bubbles within the intermediate liquid phase for two surrogates of lignocellulose (organosolv lignin, sucrose). In the hot plate reactor, a new methodology was proposed to identify and classify by size the aerosols ejected during pyrolysis of sugarcane bagasse and its pseudo-components. The aerosol studies were performed at high and low heating rates (10 ° C / s and 1200 ° C / s) and under both vacuum (150mbar) and atmospheric pressure (900mbar). The ejected aerosols were captured on glass and plastic surfaces and visualized by scanning electron microscopy (SEM). The SEM micrographs were used to estimate the ejection intensity under different conditions. These results were then used to identify relationships between bubble size and aerosol size as well as the number of bubbles vs. number of bubbles / number of aerosols used in the mathematical model. The experimental results showed that gas bubbles sizes and ejected aerosols sizes follow a lognormal distribution for all materials studied (sucrose, lignin, xylan, cellulose, and bagasse). Under vacuum conditions (150mbar) and high heating rate (1200 ° C / s) conditions, aerosol formation is promoted by enhancement of oligomer evaporation, bubble bursting, and micro-explosions within the intermediate liquid phase. The distribution of primary products and the study of kinetic parameters by using a distribution of activation energy model were performed using a hot plate reactor with a thin and uniform biomass film (thickness≈60μm). These studies were carried out under vacuum (150mbar) to minimize secondary reactions. The main compounds released during devolatilization of sugar cane bagasse were analyzed by mass spectroscopy (GC-MS), UV-fluorescence (UV-Fluorescence), gas chromatography (GC), and liquid chromatography (HPLC). The results showed that 100 °C/s, no significant changes are observed in the yields of the products due to the low thermal conductivity of the biomass and these conditions exhibited the highest yields of sugar and lignin oligomers with the least char. The bio-oil obtained at low heating rates, however, was high in water content, organic acids, aldehydes, and ketones with a lower concentration of oligomers compared with bio-oil obtained at high heating rates. The temperature profile of the external surface of the biomass was determined via experimentation and model simulation (Chapter 7). The model and experiments were compared for at different particle thicknesses, temperature, and heating rates. The reaction rate for each species was obtained by fitting experimental data to a distribution of activation energy model that describes the evolution of primary products, the main secondary reactions, bubble formation within the intermediate liquid phase, and aerosol ejection. The model predictions for aerosols char, light oxygenated compounds, and permanent gases yield were close to experimental results. The most sensitive variable for aerosols yield was particle size, showing a yield close to 0 with a 2mm particle. Temperature has a positive effect on the aerosol yield by intensifying chemical reactions and bubble dynamics (nucleation). Heating rate enhances bubble bursting and aerosol ejection but to a lesser degree than particle size.